ALAT PENDETEKSI DINI GANGGUAN SALURAN PERNAFASAN TERINTEGRASI CLOUD STORAGE - Noor, Latifah; Kosala, Gamma; Nugraha, Muhammad Mukhlis; Fitriyani, Ulfah; Imaduddin, Ilham (Program Kreativitas Mahasiswa - Karsa Cipta, 2014)
Technology advances very rapidly and currently can be implemented into every aspect of human life needs. This research seeks to take advantage of advances in technology to help meet human needs in the field of health. This tool uses the flowmeter sensor to measure the human breath that passes the sensor as input values will be processed by the system. Human breath volume value unit searched the time by using the principle of Bernoullis law of physical to detect any abnormalities in respiratory function in humans. With the possibility of it detects early these abnormalities will increase the effectiveness of treatments that can be given to sufferers. Measuring instrument is then integrated with database systems with cloud computing using the web server, so that the data collected through such tools can be sent directly to the database server and displayed through a Web page. Thus, parties concerned who have access rights to view this data can access that data anytime and anywhere. Making it easier to do preparation handling or even do prevention because it is an indication of the risk of disease can be detected early. The data can also be used as a record of statistical data for penilitian and logging that can be beneficial in the field of health. The results of this research is the integration of the two subsystems for measuring air flow and a data base of cloud computing. Hardware that is designed in such a way that it can ease of use and datas can be accessed any where are expected to provide a useful innovation which connects science in health and technology student works as a creation of Gadjah Mada UniversityKeywords : ashtma, flowmeter, cloud computingdatabase, Bernoulliâs law